Guideline for the diagnosis, treatment and long-term management of cutaneous lupus erythematosus. Issue 123 (September 2021) - Lu, Qianjin; Long, Hai; Chow, Steven; Hidayat, Syarief; Danarti, Retno; Listiawan, Yulianto; Deng, Danqi; Guo, Qing; Fang, Hong; Tao, Juan; Zhao, Ming; Xiang, Leihong; et al.
Abstract: Cutaneous lupus erythematosus (CLE) is an inflammatory, autoimmune disease encompassing a broad spectrum of subtypes including acute, subacute, chronic and intermittent CLE. Among these, chronic CLE can be further classified into several subclasses of lupus erythematosus (LE) such as discoid LE, verrucous LE, LE profundus, chilblain LE and Blaschko linear LE. To provide all dermatologists and rheumatologists with a practical guideline for the diagnosis, treatment and long-term management of CLE, this evidence- and consensus-based guideline was developed following the checklist established by the international Reporting Items for Practice Guidelines in Healthcare (RIGHT) Working Group and was registered at the International Practice Guideline Registry Platform. With the joint efforts of the Asian Dermatological Association (ADA), the Asian Academy of Dermatology and Venereology (AADV) and the Lupus Erythematosus Research Center of Chinese Society of Dermatology (CSD), a total of 25 dermatologists, 7 rheumatologists, one research scientist on lupus and 2 methodologists, from 16 countries/regions in Asia, America and Europe, participated in the development of this guideline. All recommendations were agreed on by at least 80% of the 32 voting physicians. As a consensus, diagnosis of CLE is mainly based on the evaluation of clinical and histopathological manifestations, with an exclusion of SLE by assessment of systemic involvement. For localized CLE lesions, topical corticosteroids and topical calcineurin inhibitors are first-line treatment. For widespread or severe CLE lesions and (or) cases resistant to topical treatment, systemic treatment including antimalarials and (or) short-term corticosteroids can be added. Notably, antimalarials are the first-line systemic treatment for all types of CLE, and can also be used in pregnant patients and pediatric patients. Second-line choices include thalidomide, retinoids, dapsone and MTX, whereas MMF is third-line treatment. Finally, pulsed-dye laser or surgery can be added as fourth-line treatment for localized, refractory lesions of CCLE in cosmetically unacceptable areas, whereas belimumab may be used as fourth-line treatment for widespread CLE lesions in patients with active SLE, or recurrence of ACLE during tapering of corticosteroids. As for management of the disease, patient education and a long-term follow-up are necessary. Disease activity, damage of skin and other organs, quality of life, comorbidities and possible adverse events are suggested to be assessed in every follow-up visit, when appropriate. Highlights: Evaluation of systemic involvement is needed to exclude SLE before diagnosing CLE. Assess the disease activity and damage, comorbidities and drug adverse effects. Patient education and a long-term follow-up for CLE patients are recommended. 1st-, 2nd-, 3rd- and 4th-line treatment of CLE is evidence- and consensus-based. Cautions when treating pregnant patients and pediatric patients are suggested.